Systemic Mycobacterium kansasii Infection in a Domestic Shorthair Cat. Issue 4 (August 2017) - Lee, S.-H.; Go, D.-M.; Woo, S.-H.; Park, H.-T.; Kim, E.; Yoo, H.S.; Kim, D.-Y.
Summary: A 1-year-old, female domestic shorthair cat was presented with anorexia, depression and weight loss, accompanied by multifocal nodules affecting the face, pinnae and periarticular tissue. Routine medical treatments were ineffective. The animal's physical condition continued to deteriorate and it finally died. Post-mortem examination revealed multifocal to coalescing firm nodules with occasional ulceration affecting the ears, peri-ocular areas, nasal planum, oral cavity and laryngopharyngeal region. Tan-coloured, firm, nodular lesions were also observed in the periarticular tissue, lungs and tracheobronchial and mediastinal lymph nodes. Impression smears of several of these lesions revealed a myriad of slender rod-shaped organisms, mainly in the cytoplasm of macrophages. Histopathological examination showed severe pyogranulomatous inflammation with or without necrosis in the nodules. Acid-fast staining revealed large numbers of acid-fast bacilli. Mycobacterium kansasii was detected in the tissues using multiplex polymerase chain reaction and DNA sequencing. No protozoal or fungal organisms were detected using special stains. On the basis of these results, the cat was diagnosed with systemic M. kansasii infection. To our knowledge, there have been few reports of M. kansasii infection, especially with systemic spread, in cats.